THE SUCCESS OF EMERGING CAPITAL MARKETS IN DETERMINING ECONOMIC GROWTH - Ion POHOAŢĂ; Oana R. SOCOLIUC; Delia E. DIACONAŞU (Cross-Cultural Management Journal, 2014)

(untitled)
Capital markets are regarded as “the barometer” of economic activity at the national level, but among emerging markets, the position of this segment in the economy is far from ideal. The answers that we try to offer are concerning the contribution of capital markets to the economic welfare of nations in transition from Central and Eastern Europe, using Granger causality tests. Our findings highlight that in this geographical area, the relation between capital markets and economic growth is a bidirectional one. However, although both the establishment of stock exchanges and their liberalization represented governments’ strategy of economic development, their objective was not fully achieved. Institutional transformations are required in order to attract foreign investors.